ENFORCEMENT OF LAW REGARDING ENVIRONMENTAL DAMAGE DUE TO MINING ACTIVITIES - Bidul, Sayang; Widowaty, Yeni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research discusses law enforcement regarding environmental damage due to mining activities. The research method used is sociolegal research. Research results: Mining activities not only have a positive impact on sustainable development, but mining activities also cause environmental damage, including: river water pollution, air pollution and land pollution in mining areas. Company accountability is very necessary because environmental damage that occurs needs to be repaired through the principle of absolute responsibility in Article 88 UUPLH, but recently there has been a change in the meaning of absolute responsibility in Article 88 UUPLH where the phrase without proving fault has been deleted in Law Number 6 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law so that if environmental damage occurs, it must be proven that the damage was caused by the company's mining activities. Ideally there is enforcement of Article 88 in Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law regarding strict liability regulations that companies must be absolutely responsible to the community by providing compensation in accordance with losses. suffered by the community and companies are also obliged to carry out environmental restoration.